2016
DOI: 10.1038/ejhg.2016.75
|View full text |Cite
|
Sign up to set email alerts
|

PMS2 inactivation by a complex rearrangement involving an HERV retroelement and the inverted 100-kb duplicon on 7p22.1

Abstract: Biallelic PMS2 mutations are responsible for more than half of all cases of constitutional mismatch repair deficiency (CMMRD), a recessively inherited childhood cancer predisposition syndrome. The mismatch repair gene PMS2 is partly embedded within one copy of an inverted 100-kb low-copy repeat (LCR) on 7p22.1. In an individual with CMMRD syndrome, PMS2 was found to be homozygously inactivated by a complex chromosomal rearrangement, which separates the 5'-part from the 3'-part of the gene. The rearrangement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…For most of the samples, analysis of somatic alterations is not possible as the tumors are not available. Nevertheless, complex rearrangements may have been missed in the unexplained LS cases because they are located outside of the targeted region or may be hidden in regions difficult to analyze, e.g., in common fragile site region, as it was the case in a study of Vogt et al [49] where they found a "PMS2 inactivation by a complex rearrangement involving an HERV retroelement and the inverted 100-kb duplicon on 7p22.1".…”
Section: Unexplained Ls Suspected Casesmentioning
confidence: 99%
“…For most of the samples, analysis of somatic alterations is not possible as the tumors are not available. Nevertheless, complex rearrangements may have been missed in the unexplained LS cases because they are located outside of the targeted region or may be hidden in regions difficult to analyze, e.g., in common fragile site region, as it was the case in a study of Vogt et al [49] where they found a "PMS2 inactivation by a complex rearrangement involving an HERV retroelement and the inverted 100-kb duplicon on 7p22.1".…”
Section: Unexplained Ls Suspected Casesmentioning
confidence: 99%
“…In humans, a growing cohort of neurodegenerative diseases has been attributed to DNA instability at microsatellite DNA noncanonical structures (3,4,7,(11)(12)(13)(14)(15)(16)(17)(18). Thus, replication fork barriers are believed to provoke fork stalling and template switching (FoSTeS), and microhomology-mediated break induced replication (MMBIR) (19)(20)(21)(22)(23)(24)(25)(26). The induction of gross chromosomal rearrangements (GCRs) due to FoSTeS/MMBIR has been implicated in the etiology of several developmental disorders including blepharophimosis syndrome (MIM# 110100) (23), CHARGE syndrome (MIM#214800) (27), and Pelizaeus-Merzbacher disease (MIM#312080) (28).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, oncogenic gene fusions involving the ETS (E26 transformation-specific) gene family are created in human prostate cancer by recurrent chromosomal translocation and one of the 5′ fusion partners for such translocations was identified as a HERV-K provirus [ 58 ]. A chromosomal rearrangement involving a HERV provirus has also been described in the inactivation of the mismatch repair endonuclease PMS2 gene, loss of which predisposes to mismatch repair cancer syndrome and colorectal cancer [ 59 ].…”
Section: The Case For the Prosecution: Oncogenic Properties Of Human mentioning
confidence: 99%